Hydrogeochemical characteristics and the genesis of the No. Lu 32 well in the Jiaodong Peninsula, China - Du, Guilin; Zhai, Bin; Su, Shujuan; Sui, Lailun; Chang, Xiangchun; Ren, Hongwei; Sun, Maiyu; Wang, Lili (Frontiers in Earth Science, 2023)
The No. Lu 32 well, a seismic observation well, is situated in the easternmost tip of the Jiaodong Peninsula. It is necessary to reveal the genetic mechanism of the water in this well for earthquake forecasting. By collecting water samples from the No. Lu 32 well, neighboring wells and seawater, the hydrochemical composition and main hydrogen and oxygen isotopic compositions were measured. The water type of the No. Lu 32 well is the Cl–Na type, which may be due to the influence of seawater intrusion. Hydrogen and oxygen isotopes indicate that the No. Lu 32 well and adjacent wells are mainly influenced by meteoric water, the high salinity in the water is mainly from the mixing of modern seawater, and the proportion of seawater in the water is approximately 5%. Observation data of the water temperature in the No. Lu 32 well for several years show regular annual variations.